Madrasah Amil Zakat MWCNU Gempol: Strategi Peningkatan Kompetensi Takmir Masjid dalam Pengelolaan dan Penyaluran Zakat yang Profesional - khobir, muchammad lubbil; Aliyah, Nelud Darajaatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2025)
This community service program aims to increase the capacity of mosque zakat management through training intervention of Madrasah Amil Zakat in Gempol sub-district, Pasuruan district. The Participatory Action Research (PAR) method was applied in the research by involving all participants consisting of mosque takmir in all stages, from problem identification to evaluation. The results of the service showed: an increase of about 82% in the competence of takmir in preparing digital-based zakat reports, using a standardized recording system in 67% of the assisted mosques and many mosque takmir obtained amil zakat decision letters from LAZISNU as a form of legality for zakat management. The findings contribute to the development of a community-based empowerment model by validating the effectiveness of the PAR approach in the context of Sharia financial literacy and providing an implementation framework for a short training course that is applicable to local scale zakat institutions. Challenges such as limited technological infrastructure and resistance to change are critical notes for program replication in other areas.